Development of basic technology for the manufacture of piezoelectric material for ultrasound. - Hernández Z., J. l.; Suaste G., E. (Revista Mexicana de Ingenieria Biomedica, 1991)
We present the methodology that was followed for the manufacture of piezoelectric wafers from Bario titanate, as well as its characterization.